Coupled-channel DÏ , DÎ· and DsKÂ¯ scattering from lattice QCD - RYAN, SINEAD; PEARDON, MICHAEL (My University, 2016)
We present the rst lattice QCD study of coupled-channel D , D and D s K scattering in isospin-1/2 in three partial waves. Using distillation, we compute matrices of correlation functions with bases of operators capable of resolving both meson and meson- meson contributions to the spectrum. These correlation matrices are analysed using a variational approach to extract the nite-volume energy eigenstates. Utilising L uscher's method and its extensions, we constrain scattering amplitudes in S , P and D -wave as a function of energy. By analytically continuing the scattering amplitudes to complex energies, we investigate the S -matrix singularities. Working at m 391 MeV, we nd a pole corresponding to a J P = 0 + near-threshold bound state with a large coupling to D . We also nd a deeply bound J P = 1
PUBLISHED
Cited By :3 Export Date: 6 January 2017
Keywords: lattice QCD study of coupled-channel; lattice QCD study of coupled-channel